Aktivitas Komunikasi Pemasaran Terpadu (IMC) Pemerintah Kota Ambon dalam Mengkomunikasikan Brand Ambon City Of Music Melalui Kegiatan Tiga Pilar IMC - Solsolay, Arthur (Jurnal The Messenger, 2016)
Ambon city is one of the tourist destinations in the province of Maluku, kept the charm and appeal of natural, historical, religious, culinary, education, art, culture and customs. To develop and trigger the development of musical art in the city of Ambon, Ambon city government felt the need to form a brand that became a brand differentiator and became icons of tourism in Ambon. Brand "Ambon City of Music" was initiated in hopes of becoming a starting point for the development of city Ambon become more competitive through an integrated marketing communications activities in brand communication. Research to describe and analyze the concept of the three pillars of IMC in the steps taken by the Government of Ambon in communicating the brand "Ambon City of Music". other research method used is descriptive qualitative case study approach. R esearchers found that the government has made strategic moves in IMC pillar concept is to approach audiences (government, private sector / stakeholder, elements of the community) and the media (elements of the marketing communication mix).